Accelerating And Decelerating Hypersurface-Homogeneous Cosmological Models In Barberas Second Self-Creation Theory (Global Journal of Science Frontier Research, 2012)
We study the hypersurface-homogeneous cosmological model in presence of perfect fluid within the framework of Barber's [1982, GRG, 14, 117] second self-creation theory of gravitation. We have shown that the field equations are solvable for any arbitrary cosmic scale function and then obtained exact solutions for two values of a specific parameter. While doing so, we have used the general equation of state ρ m p where m ( 1 0 ≤ ≤ m ) is a constant. We also discussed the physical aspects of the models of the universe.
Keywords: Hypersurface-homogeneous Perfect fluid Barber’s self-creation theory